Mix Method: A Model of Learning Evaluation in Traditional Pesantren - Rahman, M Saufi; Suyanto, Suyanto; Jaedun, Amat (At-tadzkir: Islamic Education Journal, 2025)
Evaluation of learning in traditional “pesantren” was rarely conducted systematically, resulting in a gap between their rich conventional practices and the need for structured evaluation instruments. Most pesantren rely on inherited kitab based on learning systems without written instructional designs, which makes it difficult to measure the effectiveness of learning objectively. This study developed the learning Islamic Boarding Evaluation Model (LIB-E Model), an evaluation framework based on the characteristics of traditional pesantren. The model had three main components: input, process and output. The method was a mixed-methods approach that adopted the Borg & Gall and Plomp development models. Data were collected through interviews, observations, questionnaires, and expert judgment. The results and findings confirmed that the LIB-E Model was both valid and reliable, with a loading factor ≥ 0.30 and Cronbach’s Alpha ≥ 0.70. The model test has a fit value that Chi Square (x2) < 2xdf, p-value > 0.05, RMSEA < 0.08. The quality is considered highly effective by practitioners and users within pesantren environments. This model was proven to be practical, efficient, and capable of providing comprehensive evaluation information, offering a contextual solution to the limitations of conventional evaluation models of learning in Islamic boarding “pesantren”.